PENERAPAN MODEL TGT UNTUK MENINGKATKAN HASIL BELAJAR IPA DAN SIKAP ILMIAH PADA SISWA KELAS V - Siti Aisyah Lubis; Lelya Hilda; Misahradarsi Dongoran (STRATEGY : Jurnal Inovasi Strategi dan Model Pembelajaran, 2026)
This study is motivated by the low learning outcomes in IPAS (Integrated Natural and Social Sciences) and students’ scientific attitudes caused by teacher-centered learning practices. Therefore, an instructional innovation through the implementation of the Teams Games Tournament (TGT) model is required. This study aims to examine whether the application of the TGT model can improve IPAS learning outcomes and scientific attitudes of fifth-grade students. This research employed Classroom Action Research (CAR) conducted through the stages of planning, action, observation, and reflection at SD Negeri 100601 Pintu Padang. The subjects of this study consisted of 16 fifth-grade students. Data were collected using tests, observations, and questionnaires. The results showed that the implementation of the TGT learning model was able to improve students’ learning outcomes and scientific attitudes. The average learning score increased from 47% in the pre-cycle with a mastery level of 25% to 89% in the second cycle with a mastery level of 81%. Students’ scientific attitudes also improved, as indicated by the increase in the average pre-test score of 49.68 to the post-test score of 75.25. Therefore, it can be concluded that the TGT learning model is effective in improving IPAS learning outcomes and students’ scientific attitudes in fifth grade. ABSTRAK Penelitian ini dilatarbelakangi oleh rendahnya hasil belajar IPAS dan sikap ilmiah siswa yang disebabkan oleh pembelajaran yang masih berpusat pada guru. Oleh karena itu, diperlukan inovasi pembelajaran melalui penerapan model Teams Games Tournament (TGT). Penelitian ini bertujuan untuk mengetahui apakah penerapan model TGT dapat meningkatkan hasil belajar IPAS dan sikap ilmiah siswa kelas V. Jenis penelitian ini adalah Penelitian Tindakan Kelas (PTK) yang dilaksanakan melalui tahap perencanaan, tindakan, observasi, dan refleksi di SD Negeri 100601 Pintu Padang. Subjek penelitian berjumlah 16 siswa kelas V. Teknik pengumpulan data menggunakan tes, observasi, dan angket. Hasil penelitian menunjukkan bahwa penerapan model pembelajaran TGT mampu meningkatkan hasil belajar dan sikap ilmiah siswa. Nilai rata-rata hasil belajar siswa meningkat dari 47% pada pra-siklus dengan ketuntasan 25% menjadi 89% pada siklus II pertemuan II dengan ketuntasan 81%. Sikap ilmiah siswa juga mengalami peningkatan, ditunjukkan oleh skor rata-rata pre-test sebesar 49,68 dan post-test sebesar 75,25. Dengan demikian, dapat disimpulkan bahwa model pembelajaran TGT efektif dalam meningkatkan hasil belajar IPAS dan sikap ilmiah siswa kelas V.